The value relevance of financial reporting standards and the accounting information prepared under specific IFRSS in Malaysia / Arun Mohamed - Mohamed, Arun (Institute of Graduate Studies, UiTM, 2012)
The thesis aims to examine the value relevance of accounting information in Malaysia. In particular it aims to determine the value relevance of accounting information produced under different financial reporting standards (IASs/MASs, MASB standards and FRSs) used in Malaysia from 1995 to 2008. It also aims to examine the value relevance of specific standards upon the adoption of IFRSs in Malaysia in 2006. The samples consist of companies listed on the Main Board of Bursa Malaysia using data obtained from the International Datastream and the annual reports. The multiple regression analyses are used to determine the value relevance of accounting information. The findings suggest that there is significant upward trend in the combined value relevance and book value but not earnings relevance. There is no significant difference in the value relevance after the introduction of the MASB standards. However, the use of FRSs in place of MASB standards exhibits higher value relevance. Earnings are more important than book value in the valuation of the firms when IASs/MASs and FRSs were used but not MASB standards.